Transforming finnish higher education: institutional mergers and conflicting academic identities - Ursin, Jani (Revista de Investigación Educativa, 2017)
As in many other European countries also Finnish higher education system has witnessed several reforms over the past decade many of which originate in efforts to make more competitive and affordable higher education system. The aim of this paper is to describe the changes and institutional mergers in particular that have taken place in Finnish higher education and explore what kind of academic identities are constructed amid changes in Finnish higher education. The paper shows that the mergers followed the objectives set by the Finnish Ministry of Education and Culture for the structural development of the higher education system and that the creation of a joint culture for merged institutions was important yet challenging. The paper also argues that due to these external changes in Finnish higher education there is a tendency to move from a traditional notion of an academic toward more hybrid and dynamic understanding of what it is being an academic in the 21st century.